Moderating role of human capital on the relationship between social network and business performance of established manufacturing small and medium enterprises / Ehsan Fansuree Mohd Surin - Mohd Surini, Ehsan Fansuree (2014)
Entrepreneurs and social network theory is an emerging area despite having grabbed most attention of the researchers in last three decades. Social network is important to the entrepreneurs to gather the important resources from the alter/s. Drawing from the social network theory and resource-based view (RBV), the purpose of this study is to investigate the relationship between social network and business performance in the established manufacturing SMEs in Malaysia. The current study also will examine the moderating role of human capital on the relationship between the social network and business performance. The research data were collected through mail and self-administered questionnaire sent to owner-manager around Malaysia. A stratified random sampling was used which elicited 226 useable responses for data analysis. Twenty hypotheses were tested in this study. First, the direct effect between the social network and business performance variables. Second, the moderating effect of human capital on the relationship between social network and business performance. The direct effect was analysed by using the hierarchical multiple regressions meanwhile the hierarchical moderated regression was used to analyse the moderator effect. Results of hierarchical multiple regressions revealed that (1) network centrality has significant positive relationship with both financial and non-financial aspects of business performance; (2) network size, family members networking and network density do not affect significantly both financial and non-financial aspects of business performance. Results from hierarchical moderated regression have shown that (1) age of entrepreneurs moderates the relationship between network centrality and non-financial aspect but not financial aspect of business performance; (2) gender moderates the relationship between network size and financial aspect but not the non-financial aspect of business performance; (3) no moderating effect of education level and work experience on both financial and non-financial aspects of business performance were found. This study enriches the body of knowledge in the area of entrepreneurship by providing the information as the use and impact of social network and human capital in Malaysian SMEs. The findings can be used also by the entrepreneurs in shaping their strategic decision for better business achievement. It is hoped that, this study will attract the attention of academicians to make further research in the social network theme especially in a developing country like Malaysia.